IMPLEMENTATION OF SCHOOL BASED MANAGEMENT IN TAMBILUNG ELEMENTARY SCHOOL - Karmila, Nita; Wijaya, Ade (UNIVERSITAS PAKUAN, 2020)
This research aims to determine the extent of the successful implementation of school-based management in Tambilung Elementary School which is one of the small schools in Bogor Regency. This research is a descriptive qualitative research that provides in-depth explanations of data and information related to the implementation of school-based management in terms of three core components namely 1) School Management, 2) Active, Creative and Enjoyable Learning, and 3) Community Participation. From the results of the study it can be concluded that the implementation of school-based management in Tambilung Elementary School has only reached 83.62% which, if elaborated, the success of each component, namely: the school management component 85.89%, the learning activity component amounted to 76.19% and the component of community participation in the implementation of school-based management is 88.80%.